0180 Sleep, Sleepiness, and Sleep Hygiene Related to Nomophobia (No Mobile Phone Phobia). (27th May 2020) - Peszka, J; Michelle, S; Collins, B T; Abu-Halimeh, N; Quattom, M; Henderson, M; Sanders, M; Critton, J; Moore, B; Mastin, D F
Abstract: Introduction: Previously, active phone use at bedtime has been implicated in disrupted sleep and related complaints. To improve sleep, a recommendation following such findings is limiting phone use before and during bedtime. However, for those with the characteristic of "nomophobia", fear of being out of mobile phone contact, this recommendation could exacerbate anxiety at and around bedtime and disrupt, rather than improve, sleep. In 2012, an estimated 77% of 18-24-year-olds could be identified as nomophobic. Because of the prevalence of nomophobia and its possible interaction with sleep, we explored the existence of nomophobia in a college-age population and its relationship to sleep, sleepiness, and sleep hygiene behaviors. Methods: 327 university students (age: M=19.7 years, SD=3.78) recruited from introductory psychology courses and campus newsletters were given extra credit or a chance to win $25 gift cards for participation. Participants completed demographic information, the Nomophobia Questionnaire (NMP-Q), the Epworth Sleepiness Scale (ESS), the Pittsburgh Sleep Quality Index, questions regarding associated features of inadequate sleep hygiene, and the Sleep Hygiene Index. Additional sleep hygiene questions assessed frequency of active and passive technology use during sleep time. Results: 89.4% of the participants had moderate or severe nomophobia. Greater nomophobia was significantly related to greater daytime sleepiness (ESS) ( r (293)=.150, p <.05), associated features of poor sleep (daytime sleepiness: r (297)=.097, p <.05, and avolition: r (297)=.100, p <.05), more maladaptive sleep hygiene behaviors including active technology use during sleep time ( r (298)=.249, p <.05), long daytime naps, inconsistent wake and bed times, using bed for non-sleep purposes, uncomfortable bed, and bedtime cognitive rumination ( r 's=0.097 to 0.182). Conclusion: Most participants experienced moderate to severe nomophobia with greater nomophobia associated with greater sleepiness, avolition, and poorer sleep hygiene. Nomophobia is likely to be an important consideration when treating sleep disorders and/or making any sleep hygiene recommendations. Support: Hendrix College Charles Brewer Fund for Psychology